Processing magnetic sensor array data for AC current measurement in multiconductor systems - D'Antona, G.; Di Rienzo, L.; Ottoboni, R.; Manara, A. (IEEE transactions on instrumentation and measurement, 2001)
The continuous progress in magnetic sensor research provides increasing accuracy in measurement systems based on magnetic sensor arrays. Many industrial applications in the field of protection for low-voltage electrical systems require novel technologies of AC current sensors characterized by lower costs and wider measuring range in amplitude and frequency. For this purpose, a promising solution is the utilization of sensor arrays provided with signal processing techniques. In the paper, we propose a new principle for simultaneous measurement of polyphase currents flowing in parallel conductors of arbitrary cross-sections based on processing magnetic sensor signals. After describing the analytical solution of the measurement problem, theoretical uncertainty analysis is carried out. Preliminary experimental results confirm the validity of the new approach.